A Psycho-Sociolinguistic-Based Project-Based Learning Model for Arabic Language Learning: A Case Study at MTs Al-Ma’arif Rakit Banjarnegara - Fatur Fahrezi; Irfan Musonif; Helmi Salma Labibah; Muhamad Ibnu Athoillah; Abdul Munip (Abjadia : International Journal of Education, 2026)
The low level of students’ communicative competence remains a major challenge in Arabic language learning across various educational levels in Indonesia. Learning practices that primarily emphasize memorization of grammar and vocabulary have not sufficiently addressed learners’ psychological and social dimensions. This study aims to develop and empirically validate a psycho-sociolinguistic-based Project-Based Learning (PjBL) model for Arabic language learning. Employing a descriptive–analytical design, the study involved both conceptual analysis and empirical validation. The empirical phase utilized a quasi-experimental one-group pretest–posttest design conducted at MTs Al-Ma’arif Rakit Banjarnegara, involving 32 eighth-grade students. Research instruments included a communicative competence test, a psycho-sociolinguistic questionnaire, and classroom observation sheets. The findings reveal significant improvements in students’ communicative competence, particularly in sociolinguistic and strategic aspects, along with increased learning motivation, self-confidence, and quality of social interaction. The integration of psycho-sociolinguistic principles into the stages of PjBL effectively fosters contextual, meaningful, and humanistic Arabic language learning. Therefore, the psycho-sociolinguistic-based PjBL model is empirically proven to be effective in real classroom contexts and holds strong potential for broader implementation in madrasah-based Arabic language education. The developed model contributes theoretically by integrating affective and sociolinguistic perspectives into project-based pedagogy, and practically by offering an adaptable framework for improving communicative competence in madrasah-based Arabic education.